Analysis of Knowledge, Higher-Order Thinking Skills, and Compiling Evaluations for MA Biology Teachers in Pati Regency - Masru'ah, Masru'ah; Bintari, Siti Harnina; Alimah, Siti (Journal of Innovative Science Education, 2022)
The thing that biology teachers must pay attention to in educating students to be able to think at higher-order is the mastery of the teachers' knowledge in biology material, the teachers' higher-order thinking skills, and their ability to develop HOTS in the learning process. When the teachers possess them, the teacher can create and develop an effective HOTS learning class. The purpose of this study was to analyse the ability of knowledge (factual, conceptual, procedural, and metacognitive), higher-order thinking (analysing, evaluating, and creating), and activities to design HOTS-oriented evaluations for Madrasah Aliyah teachers in Pati Regency. This study uses a mixed-method approach with a sequential explanation method. The research population includes members of the MA Biology MGMP in Pati Regency, totalling 35 people. The results showed that 1) MA teachers in Pati Regency had high-level knowledge and thinking skills in ecosystem concepts in the sufficient category, and 2) the ability to compile a HOTS-oriented biology learning evaluation was in a good category.